Co3O4 Hollow Nanoparticles Embedded in Mesoporous Walls of Carbon Nanoboxes for Efficient Lithium Storage - Huang, Yi; Fang, Yongjin; Lu, Xue Feng; Luan, Deyan; Lou, Xiong Wen (David) (Angewandte Chemie International Edition, 2020)
Confining nanostructured electrode materials in porous carbon represents an effective strategy for improving the electrochemical performance of lithium‐ion batteries. Herein, we report the design and synthesis of hybrid hollow nanostructures composed of highly dispersed Co3O4 hollow nanoparticles (sub‐20 nm) embedded in the mesoporous walls of carbon nanoboxes (denoted as H‐Co3O4@MCNBs) as an anode material for lithium‐ion batteries. The facile metal–organic framework (MOF)‐engaged strategy for the synthesis of H‐Co3O4@MCNBs involves chemical etching‐coordination and subsequent two‐step annealing treatments. Owing to the unique structural merits including more active interfacial sites, effectively alleviated volume variation, good and stable electrical contact, and easy access of Li+ ions, the H‐Co3O4@MCNBs exhibit excellent lithium‐storage performance in terms of high specific capacity, excellent rate capability, and cycling stability. Hybrid hollow architectures composed of highly dispersed Co3O4 hollow nanoparticles embedded in the walls of mesoporous carbon nanoboxes (H‐Co3O4@MCNBs) are synthesized through an elaborate etching‐pyrolysis‐oxidation strategy starting from ZIF‐67 nanocubes. The H‐Co3O4@MCNBs obtained exhibit excellent lithium storage properties as an anode material.